Rental Value of a Local Government Asset Using Asymmetric Valuation - Difa(1), Farach; Makhfatih(2), Akhmad; Khasanah(3), Uswatun; Dwiputri*(4), Inayati Nuraini (Universitas Prasetiya Mulya, 2019)
This study tried to identified the market and the rental value of Grha Z as one of the local assets in Province A. This study used cost approach and income approach in valuation to obtain rental value and Net Present Value (NPV) of the building, the construction cost of a new Grha Z building, management office, home generator, and warehouse. Because of the limited information, this study valuates the asset asymmetrically. The result of the calculation produces the value of assets, taxable value assets as the basis for calculating the value of the rental assets according to Minister of Finance (MoF) Regulation 33/2012. The results showed that the rental value of local assets such as land and buildings in the area Grha Z can be increased by Regulation of Indonesian MoF Number 33/2012. It can be used as a materialconsideration in the improvement of regional asset rental agreement.Keywords: rental value, income approach, cost approach, local asset(1) Fakultas Ekonomika dan Bisnis Magister Ekonomika Pembangunan, Universitas Gadjah Mada, Indonesia(2) Fakultas Ekonomika dan Bisnis, Universitas Gadjah Mada, Indonesia(3) Fakultas Ekonomi dan Bisnis, Universitas Ahmad Dahlan Yogyakarta, Indonesia(4) Fakultas Ekonomi, Universitas Negeri Malang, Indonesia* Corresponding Author https://doi.org/10.21632/irjbs.12.1.31-39